Expressing an intentional state - Kemmerling, Andreas (Speech acts, mind, and social reality, 2002)
I don’t have any serious quarrels with John Searle’s approach to speech act theory.1 There’s a lot of little things that I do not really understand. (Example: what is a direction of fit?) There are a few minor points which I think are wrong. (Example: the doctrine about “underlying rules” which are “manifested or realized” by conventions, and, to be frank, the whole thing about so called constitutive rules. Why should a statement like “Greeting in a normal context counts as a corteous recognition of the addressee by the speaker” be regarded as conveying a rule? How could one violate, or follow, the alleged rule? Maybe greeting is something which presupposes the existence of certain rules, or maybe statements of the type “x counts as y in context c” are true only in virtue of the fact that certain policies are accepted in the contexts in question, but the statement above, concerning the essence of greeting, is not the statement of a rule.)
Gesehen am 04.11.2020